Awareness of glycosylated haemoglobin (HbA1c) among type 2 diabetes mellitus patients in Hospital Putrajaya - Samsudin, Intan Nureslyna; Chellappah Thambiah, Subashini; Wan Mohammed Ayub, Wan Mohamad Asyraf; Ng, Wan Cheng; Hussein, Zanariah; Mohd Noor, Nurain; Mohamad, Masni; George, Elizabeth (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
The glycosylated haemoglobin (HbA1c) test is the most widely accepted laboratory test for evaluating long term glycaemic control. Patient’s understanding of HbA1c can lead to better glycaemic control. This study is aimed to determine the awareness and level of understanding of HbA1c among type 2 DM patients and its association with glycaemic control. A cross-sectional descriptive study among Type 2 DM patients undergoing routine follow up in an endocrine clinic of a tertiary centre in Malaysia. Patients were invited to answer a validated questionnaire which assessed their awareness and understanding of HbA1c. Their last HbA1c results were retrieved from the laboratory information system. A total of 92 participants were recruited. Fifty-six (60.9%) were aware of the term HbA1c. Fifty percent were categorised as having good HbA1c understanding, with age, monthly income and level of education between HbA1c understanding and glycaemic control, although more patients with good HbA1c understanding had achieved the target glycaemic control compared to those with poor understanding. The level of HbA1c awareness and understanding was acceptable. Factors associated with understanding were age, income and level of education. Continuing efforts however, must be made to improve patients understanding of their disease and clinical disease biomarkers.